ETHICAL PRINCIPLES FOR ORGANIZING DIGITAL INVESTIGATION UZBEKISTAN AND FOREIGN EXPERIENCE - Khamidov Bakhtiyor Khamidovich (International Journal of Business, Law and Political Science, 2024)
This article discusses the ethical (etiquette) issues of organizing a digital investigation in the process of digital transformation. In particular, the study put forward proposals for improving the methodological support of investigative practice in the conduct of digital investigation. The study analyzed the experience of Germany, England and the Republic of Uzbekistan in implementing the rules of digital ethics (etiquette). The researcher puts forward the idea that in the process of digital transformation, it is fundamentally important to introduce ethical (etiquette) rules for organizing digital investigation into investigative practice. The author believes that in order to protect personal data during investigative activities in the digital environment, first of all, it is necessary to establish ethical (etiquette) principles for working with electronic evidence, therefore, he gives recommendations on adapting investigative practice to advanced foreign practices. The article was prepared on the basis of scientific and practical research, the opinions of theorists and practitioners on ethical (etiquette) issues of digital investigation in the process of digital transformation.